PENGARUH TEKNOLOGI INFORMASI SMART KAMPUS, IMPLEMENTASI SISTEM MANAJEMEN MUTU ISO 9001:2008 DAN SKIL KEPEMIMPINAN TERHADAP KNOWLEDGE MANAGEMENT, MOTIVASI KERJA DAN KINERJA DOSENUNIVERSITAS NEGERI PADANG - Rino Rino; Sulastri Sulastri; Idris Idris (Program Studi Magister Manajemen, 2013)
Abstract This study aimed to analyze the influence of smart campus information technology assessment, implementation of ISO 9001:2008 quality management system, the knowledge management skills of leadership and motivation of faculty performance UNP. The study population is a lecturer at the State University of Padang. The sample size was determined based on the requirements of SEM analysis using maximum likelihood estimation model to obtain the 175 respondents with randome proportional sampling technique. Data were analyzed using structural equation modeling software AMOS19. The results of the study is the assessment of smart information technology campuses significant effect on knowledge management, leadership skills significantly influence the Management of knowledge, leadership skills significant effect on faculty performance, and motivation significantly influence the performance of the lecturer. Key word: performance, knowledge management, work motivation, leadership skill, quality management system, information technologhy